"The political philosophy than Kant did not write" the potential for politics and political community in Kant's third critique - Malabed, Rizalino Noble (2015)
In his Critique of Judgement, Immanuel Kant claims that judgement provides (1) a transition from the theoretical to the practical and unifies philosophy and (2) the principles for an alternative politics and founds the ideal political community. Vital to understanding Kant’s second claim is the idea of sensus communis, which arises from his contention that the judgement of taste appears as universal because taste not only presupposes common sense but is also community sense. This article shows that in his discussion, which moves from reflective judgement, to the judging subject, and to the sensus communis, Kant argues for a potential for politics and a sense of political community wherein the two claims on judgment imply each other.
Keywords: Political philosophy